Strategi Agen Transfer Kebijakan Tingkat Lokal Menuju Kota Layak Anak - Arissa, Yeni (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Brawijaya, 2022)
The child-friendly City (KLA) policy has been running for almosttwo decades. However, the problems of children in the regions are increasingly diverse and increasing. Child prostitution is rampant, the stunting rate is very high, the dropout rate is very high, the dropoutrate is increasing during the covid-19 pandemic, the proliferation of street children, the increase in child sexual development, the problem of learning to be brave, and others.This study aims to find out whether local agents understand the transferability of KLA policies so that they cannot optimally implement the Minister of Women’s Empowerment Regulation No 2 of 2009 concerning child-friendly district/city policies. Considering this KLA is a transferred policy upon the ratification of the convention on the rights of the child. So that to meet this nee, local agent do not have the ability to built systems that directly solve real problems of children in the field.Inventory of local agents has been carried out in the phenomenon of transfer policies involved in child-friendly city (KLA) policies in Pontianak City. With the theoretical framework to transfer policy (Dolowitz and Marsh, 19990, deepening knowledge about the transferability of the policy in terms of benefits, adjustments, and past policies (Sobari,2011). In Addition, this study reveals the ability of local agents to carry out a strategy in transfer policy as the theoryexspressed by Mauricio I. Dussauge-Laguna (2019).This qualitative research uses the case study method. Sources of data form documentation, archives, and structured interviews to adapt the transfer policy framework. The focus of the research is the perspective and movement of ideas by KLA agents in the regions. Thsis study strengthens the transfer policy theory whose phenomenon can explain the abilityof local agents who are resistant to policies originating from the international world due to the influence and assessment of domestic agents who become liaisons for global agents in the central government. So empirically, local agents are needed to master policy development strategies to be more targeted and collaborative in drawing policies. Good with conceptual strategies, capacitybuilding, fine-tuning, and persuasion.